Prognosis of Traumatic Diaphragmatic Injury in Dhaka Medical College Hospital, Dhaka - Goni, Mohammad Osman; Alam, Md Kamrul; Hossain, Mosharraf; Das, Debasish; Islam, Mohammad Aminul; Mahmud, Hossain Al (Journal of Dhaka Medical College, 2023)
Introduction: Diaphragmatic injuries include wounds and diaphragmatic ruptures due to thoracoabdominal blunt or penetrating trauma. Their incidence ranges between 8 and 15%. The diagnosis is often delayed despite several medical imaging techniques. The mortality is mainly related associate Injury. Aims: The aim of our study was to evaluate the prognosis, after surgery of our patient with diaphragmatic injury. Patients and methods: We performed a prospective study over a period of two years, between January 2018 December 2019, at the department of thoracic surgery of Dhaka Medical College Hospital, Dhaka, Bangladesh. All patients diagnosed with diaphragmatic injury were included in this study. Each patient operated because traumatic diaphragmatic injury was evaluated in respect of age, sex, nature of injury, preoperative examination findings, laboratory test results, imaging methods, time of diagnosis, operation findings, concomitant injures to other organs, operations performed, length of stay in hospital and development of postoperative morbidity and mortality. Results: Over the study period, 22 cases of diaphragmatic injuries were included. The female was 4 and 18 was male. The mean age of male patients 29.2±12.1 and female 28±11.6 years. RTA with blunt trauma chest was 12, 6 was fall from height and 5 were stab injuries. The most common injuries concomitant to traumatic diaphragmatic rupture were a haemothorax, rib fracture, stomach, colon, liver and spleen. Three patients developed wound infection and two patients died. Conclusion: In high energy blunt and penetrating thoracoabdominal trauma, diaphragmatic injures should be suspected. An emergency thoracotomy or laparotomy followed by reposition of abdominal organ and repair of the defect of the diaphragm is the gold standard for the management of these cases. J Dhaka Med Coll. 2021; 30(2) : 131-135